Development and quality evaluation of spray dried probiotic flavoured yoghurt containing Lactobacillus Bulgaricus - SREEKUTTY SURESH V; Dr. Rajesh G.K (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and quality evaluation of spray dried probiotic flavoured yoghurt containing Lactobacillus Bulgaricus
Development and quality evaluation of spray dried probiotic flavoured yoghurt containing Lactobacillus Bulgaricus